Considerations for science and technology policies in the context of Amazon sustainability (Sustainability in Debate, 2024)
This paper presents a brief overview of Science and Technology in the Amazon from a regional perspective. We discuss the role of universities, scientific and technological institutions, and centres of knowledge, and we elaborate on the challenges of mobilising these institutions for sustainable territorial development, considering some territorial attributes and regional actors. For this purpose, we used national data and indicators of postgraduate studies, investments, and geographical distribution of Public Teaching and Research Institutions in the Amazon. Finally, we present paths for developing a regional Science and Technology strategy. We conclude that, despite considerable advances in recent decades, we still face a reality of insignificant investments in the region. It is imperative to have a project that incorporates Science, Technology, and Innovation into productive dynamics capable of shaping a new development model in the Brazilian Amazon.